2011
DOI: 10.7763/ijeeee.2011.v1.36
|View full text |Cite
|
Sign up to set email alerts
|

Customer’s Adoption of Mobile-Commerce A Study on Emerging Economy

Abstract: Abstract-Today, mobile communication technologies provide immense additional scope for consumers' banking transactions due to their always-on functionality and the option to access bank's facilities anytime and anywhere. Mobile banking is a subset of electronic banking which underlies not only the determinants of the banking business but also the special conditions of mobile commerce. It is the latest and most innovative service offered by the banks. But not enough study has been done to known regarding how cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
(44 reference statements)
4
17
3
Order By: Relevance
“…This outcome is incompatible with some previous empirical studies. For example, it has been found that awareness has a positive influence on intention to adopt mbanking [106]. However, the results of this study indicate that the majority of participants have a low level of awareness about m-government applications because they do not have knowledge or information about these applications.…”
Section: Discussioncontrasting
confidence: 52%
“…This outcome is incompatible with some previous empirical studies. For example, it has been found that awareness has a positive influence on intention to adopt mbanking [106]. However, the results of this study indicate that the majority of participants have a low level of awareness about m-government applications because they do not have knowledge or information about these applications.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies revealed that perceived risk was considered as a major factor preventing consumers from adopting an innovation in general and mobile commerce in particular [29,31]. As shown by Lu et al [30], approximately 75% of consumers today worry about security and transaction risks.…”
Section: Perceived Risk and Perceived Cost Of Using Nfc Mobile Paymentsmentioning
confidence: 96%
“…A number of scholars have equally reported that the easiness that is associated with IS/IT based services such as social networking (Wamba, et al, 2017), e-government (Carter et al, 2016;Susanto & Aljoza, 2015), e-insurance (Leeet al, 2015) and mobile banking (Safeena et al, 2011) is a core determinant of adoption of these latest technology trends. The essence of these findings indicate that the absence of face-to-face interaction that is common in an internet enabled services platforms such as mobile commerce requires such platform to be easily used with regards to user friendliness as this will reduce the difficulty that may be associated with the usage of the services (Chong et al, 2010).…”
Section: Discussionmentioning
confidence: 99%